Contradiction as insight: autoethnography, narrative inquiry, and decolonizing educational research in Jamaica - Powell, Paula (Frontiers in Education, 2025)
This article explores the methodological possibilities of autoethnography and narrative inquiry in addressing colonial legacies in Jamaican education. Situated within postcolonial theory and culturally responsive teaching (CRT), it examines how reflexive and storied approaches can contribute to decolonizing educational research. Rather than reporting new empirical findings, the article undertakes a conceptual analysis. It draws on autoethnographic reflection and published Jamaican scholarship to interrogate how research methodologies themselves may reproduce or resist colonial epistemologies. Clandinin and Connelly’s three-dimensional narrative inquiry space, which focuses on temporality, sociality, and place, provides a conceptual orientation, highlighting how storied inquiry foregrounds the entanglement of subjectivity, history, and culture. The analysis develops four insights that demonstrate how contradiction can serve as a methodological resource in decolonizing research. Reflexivity situates positionality at the center of knowledge production. Narrative complexity resists reductive simplification and holds tensions within stories. Divergence between theory and practice is reframed as a generative condition rather than a shortcoming. Counter-stories disrupt colonial narratives by affirming cultural identities and resisting deficit framings. Autoethnography and narrative inquiry, when situated within postcolonial and culturally responsive perspectives, operate as decolonizing methodologies. They challenge Eurocentric assumptions, amplify marginalized voices, and embrace complexity. While Jamaica provides the illustrative case, the argument extends globally to postcolonial and marginalized contexts. By conceptualizing contradiction as insight, the article contributes a novel perspective to debates on decolonizing methodology, emphasizing reflexivity, complexity, divergence, and counter-stories as foundations for inclusive educational inquiry.